Pemanfaatan Batu Sungai Budong-Budong Kabupaten Mamuju Tengah Dalam Campuran AC-WC - Chornelius Sapan; Mangontan, Robert; Boro, Wona Grace (Universitas Kristen Indonesia Paulus, 2025)
Central Mamuju Regency was formed in 2013 as a result of the expansion of Mamuju Regency, with the aim of improving government services and accelerating development in the region. Central Mamuju has its capital in Tobadak. The purpose of this study is to identify the properties aggregates from the Budong-budong River and assess their feasibility in AC-WC mixtures based on the 2018 Bina Marga specifications. The research method involves laboratory testing of aggregate, asphalt, and filler characteristics, as well as conventional Marshall and Marshall Immersion tests to assess the stability and durability of the mixture. The results showed that the Budong-budong River aggregate has characteristics that meet the 2018 Bina Marga standards, obtained a Stability value of 1559.56 kg, a flow value of 3.18 mm, a VIM value of 4.54%, a VMA value of 19.34%, a VFB value of 76.51% with Marshall Remaining (SMS) stability reaching 93.88% at an optimum asphalt content of 6.5%.